The Sosialisasi Undang-Undang Harmonisasi Peraturan Perpajakan Sebagai Sarana Pendidikan Pajak Siswa Smk Poncol Jakarta - Aulia Hidayati; Ratih Pratiwi; Mela Nurdialy (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Early tax education for school students needs to be carried out to increase awareness and tax compliance. Vocational High School (SMK) students are part of the younger generation of future taxpayers. In 2021, there will be changing tax regulations with the Harmonization of Tax Law (UU HPP). The Lecturer of the Accounting Study Program at the Vocational School of IPB held community service activities by socializing the UU HPP to students majoring in Accounting at SMK Poncol Jakarta. This activity aims to increase the understanding of taxation, especially income tax and Value Added Tax, for students at SMK Poncol Jakarta. The implementation of activities uses lecture and simulation methods and evaluates activities through pre-test and post-test questionnaires to determine the success of tax socialization. Based on the test results, After the tax socialization, 90.7% of students answered that they understood about PPh and VAT; 91.67% of students know income tax (PPh), and there are 86.25% of students know VAT. Generally, tax socialization activities increase students’ understanding of taxes and UU HPP.